Ozone Therapy and Its Scientific Foundations (Ozone Therapy Global Journal, 2012)
In recent years, ozone therapy as an effective therapeutic method has become moredeveloped and well known. Russia and Cuba have recognized it in their legislation; itis regulated in more than 76% of the Autonomous Regions of Spain; and in Italy fourRegions have specified the criteria for practicing it, in addition to two favorable courtdecisions. Ozone therapy is characterized by the simplicity of its application, its greateff ectiveness , good t olerance, and by t he virtual absence of side effect s. Thisdocument, based on the latest books and scie ntific articles on the subject, updatesthe recent fi ndings t hat j ustif y, from the scie ntific point of view, the medical u se o fozone . F or ma ny years the applic atio n of ozone in medical practi ce was not wellaccepted due to unfounded ideas about its toxicity in relation to the high concentrationsused in industry. As with any healing technique, ozone therapy is dependent on thedosag e. It i s impor tant to understand that in clinical practice th e conc entr ations o fozone are lower tha n the toxic levels by severa l orders of magnitude . In thisconcentration r ange, the oz one acts as a t herape utic sub stance and pres entsimmunomodulat i ng, anti-inflammato ry, bactericide, antiviral, fungicide, analgesicproperties and others. There are an in creasin g number of scientific so cieties andclinical papers, including m eta-analysis studies. At the same time efforts are beingreinforced to regularize this medical practice.